Rates of tree cover loss in key biodiversity areas within Indigenous Peoples’ lands - Simkins, A.T.; Donald, P.F.; Beresford, A.E.; Butchart, S.H.M.; Fa, J.E.; Fernández-Llamazares, Á.; Garnett, S.T.; Buchanan, G.M. (Wiley, 2024)
Indigenous Peoples’ lands (IPL) cover at least 38 million km2 (28.1%) of the global terrestrial surface. These lands can be important for biodiversity conservation. Around 20.7% of IPL intersect areas protected by government (PAs). Many sites of importance for biodiversity within IPL could make a substantial but hitherto unquantified contribution to Global site-based conservation targets. Key Biodiversity Areas (KBAs) represent the largest global network of systematically identified sites of high importance for biodiversity. We assessed the effectiveness of IPL in slowing biodiversity loss, both within and outside PAs, by quantifying tree cover loss in KBAs at international and national levels and comparing it with losses at equivalent sites outside mapped IPL. Based on a matched sample of 1-km2 cells in KBAs inside and outside of mapped IPL, tree cover loss in KBAs outside of PAs was lower inside IPLs when compared to outside mapped IPLs. By contrast, tree cover loss in KBAs inside of PAs was lower outside mapped IPLs than inside IPLs (although the difference was far smaller). However, national rates of tree cover loss in KBAs varied greatly in relation to their IPL and PA status. In half of the 44 countries we examined individually, there was no significant difference in the rate of tree cover loss in KBAs inside and outside mapped IPL. The reasons for this inter country variation could help understand the importance of IPL in meeting the CBD's ambition of conserving 30% of land by 2030. Critical to this will be coordinated action by governments to strengthen and enforce Indigenous Peoples' rights, secure their collective systems of tenure and governance, and recognize their aspirations for their lands and futures.